The effect of transmit B1 inhomogeneity on hyperpolarized [1‐13C]‐pyruvate metabolic MR imaging biomarkers. Issue 9 (10th August 2021) - Harlan, Collin J.; Xu, Zhan; Walker, Christopher M.; Michel, Keith A.; Reed, Galen D.; Bankson, James A.
Abstract: Purpose: A specialized Helmholtz‐style 13 C volume transmit "clamshell" coil is currently being utilized for 13 C excitation in pre‐clinical and clinical hyperpolarized 13 C MRI studies aimed at probing the metabolic activity of tumors in various target anatomy. Due to the widespread use of this 13 C clamshell coil design, it is important that the effects of the 13 C clamshell coil B1 + profile on HP signal evolution and quantification are well understood. The goal of this study was to characterize the B1 + field of the 13 C clamshell coil and assess the impact of inhomogeneities on semi‐quantitative and quantitative hyperpolarized MR imaging biomarkers of metabolism. Methods: The B1 + field of the 13 C clamshell coil was mapped by hand using a network analyzer equipped with an S‐parameter test set. Pharmacokinetic models were used to simulate signal evolution as a function of position‐dependent local excitation angles, for various nominal excitation angles, which were assumed to be accurately calibrated at the isocenter. These signals were then quantified according to the normalized lactate ratio (nLac) and the apparent rate constant for the conversion of pyruvate to lactate (kPL ). The percent difference between these metabolic imaging biomarker maps and the reference value observed at the isocenter of the clamshell coil was calculated to estimate the potential for error due to position within the clamshell coil. Finally, regions were identified within the clamshell coil where deviations in B1 + field inhomogeneity or imaging biomarker errors imparted by the B1 + field were within ±10% of the value at the isocenter. Results: The B1 + field maps show that a limited volume encompassed by a region measuring approximately 12.9 × 11.5 × 13.4 cm (X‐direction, Y‐direction, Z‐direction) centered in the 13 C clamshell coil will produce deviations in the B1 + field within ±10% of that at the isocenter. For the metabolic imaging biomarkers that we evaluated, the case when the pyruvate excitation angle (θP ) and lactate excitation angle (θL ) were equal to 10° produced the largest volumetric region with deviations within ±10% of the value at the isocenter. Higher excitation angles yielded higher signal and SNR, but the size of the region in which uniform measurements could be collected near the isocenter of the coil was reduced at higher excitation angles. The tradeoff between the size of the homogenous region at the isocenter and signal intensity must be weighed carefully depending on the particular imaging application. Conclusion: This work identifies regions and optimal excitation angles (θP and θL ) within the 13 C clamshell coil where deviations in B1 + field inhomogeneity or imaging biomarker errors imparted by the B1 + field were within ±10% of the respective value at the isocenter, and thus where excitation angles are reproducible and well‐calibrated. Semi‐quantitative and quantitative metabolic imaging biomarkers can vary with position in the clamshell coil as a result of B1 + field inhomogeneity, necessitating care in patient positioning and the selection of an excitation angle set that balances reproducibility and SNR performance over the target imaging volume.